Renovasi Sistem Menuju Ekonomi Rakyat Berkeadilan - Engkos Achmad Kuncoro (Bina Nusantara University, 2004)
Economic crisis in Indonesia emerges as an effect of economic policy with much rely on conglomerates and disregard people economics in capitalistic economy system. Since 1998, the awareness of reforming economic system strives to the democratic economics are not yet realized by the government of reform era. The state has failed to improve the economics in agricultural sector especially the farmers, who has systematically experience of poverty. The new governance lead by the elected president have to conduct the farmer economic institution becomes part of integrated network of the rural ecomomic and the conglomerates, and have to be supported by macro economic policies having conducive for improving the people economics.